Civil society organizations and Zimbabwe’s post Mugabe re-engagement efforts with USA, agency or obstruction? - Pasipamire, C. T. (BUSE, 2019)
Civil society entails the space between the family, the state and business. The concept of civil society which goes as far back as Aristotle, has of late grown in influence and scholarly interest. It is interesting to note that civil society has spread its influence beyond state boundaries, dabbling in international affairs. The purpose of the study was to explore the role of CSOs as non-state actors in Zimbabwe’s re-engagement efforts with the United States of America in the post-Robert Mugabe era, now popularly referred to as the Second Republic. The objectives of this study were to examine the CSOs-State relations in the post Mugabe Zimbabwe, to analyze the role of CSOs in Zimbabwe’s post Mugabe re-engagement efforts with USA and to assess the impact of CSOs roles in Zimbabwe’s re-engagement efforts with USA. Basing on constructivism and liberalism as a theoretical foundation, the research considered the influence of CSOs in international relations and how they can influence events on a global stage. Using qualitative methods, the population comprised of 13 key informant interviews. The participants for the study were drawn from civil society organizations that specifically deal with the Government of Zimbabwe. Documentary search was also used to review scholarly literature on the subject. The key findings of this research revealed that CSOs are very much involved in various strategies and roles for promoting international re-engagement of Zimbabwe and the global community. These strategies include lobbying, producing various papers and publications on re-engagement, devising alternative policy frameworks for Zimbabwe’s economic and political reforms, promoting democratization, promoting co-operation, partnerships, enhancing reconciliation between political parties in Zimbabwe, endorsing national dialogue and exercising preventive diplomacy. The research findings also revealed the evil side of CSOs such as pushing for regime change, how they promote sectorial interests, how they are using the internet to exert their influence on governments. From the study, it was concluded that CSOs are divided into pro-second republic loyalists and pro-west whose funding comes from the west and thus perpetuating the already polarized efforts to facilitate Zimbabwe’s re-engagement. The study concluded by recommending that Zimbabwe’s path to engaging and re-engaging the West should also include opposition parties, students, think tanks, the Diasporan community and basically all stakeholder communities in Zimbabwe
Keywords: Civil society organization; Re-engagement; Non-Governmental Organizations; Power; Diplomacy; Politics